Partisipasi Politik Muslimah dalam Pandangan Yusuf Qardhawi - Rashda Diana (Universitas Darussalam Gontor, 2009)
The role sahabiyyat companions of the Holy Prophet Muhammad PBUH has given many examples in political participation. These political dimensions may be seen from their activities. All political roles of female companions of the Messenger of Allah is considered as the implementation of Muslimah politics at the time being. Yusuf Qardhawi is among vew Muslim scholars who concerns upon the role and participation of Muslimah in politics. In the view of Qardhawi, Islam has practiced democracy to lay on the principle and norms of democracy itself. A Muslimah supports democracy with consideration that democracy is a mechanical authority to actualize the political principles of Islam, such as in the leadership election, organizational consultation, a media of commanding the truth and avoiding the false, against tyrannies and avoiding the vise , particularly at the unbelieving in Allah. Even though, the political participation of a Muslimah has faced many obstacles external as well as internally.